FATHERLESS: LUKA TERSEMBUNYI AKIBAT PERCERAIAN YANG MEMPENGARUHI PERILAKU REMAJA - Shania Aulia Rahmania Anshary; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
One of the countries included in the fatherless country category is Indonesia. The term "fatherless" refers to a situation in which a child has a father, but the father does not actively play a role or is absent in the process of development and growth of the child. There are various causes of fatherless, one of which is caused by the divorce of both parents. The number of children who experience fatherless due to divorce has an impact on negative adolescent behavior. The purpose of writing this study is to dig deeper into the impact and wounds hidden by adolescents from their parents caused by fatherless divorce. Also to investigate how the presence or absence of fathers can affect adolescent behavior. The method used from this research is a qualitative method that is a library research, which is collecting data in accordance with the theme discussed. The results of journal research that have been analyzed, it can be concluded that the impact of fatherless due to divorce on adolescent behavior is loneliness, sadness, trauma, juvenile delinquency, decreased achievement and difficulty controlling emotions.